2011
DOI: 10.1007/s11999-011-1777-2
|View full text |Cite
|
Sign up to set email alerts
|

A Squeaky Reputation: The Problem May Be Design-dependent

Abstract: Our findings complement the theory from in vitro studies suggesting that neck impingement on the elevated titanium rim is the probable cause of the increased frequency of squeaking with this design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 42 publications
1
39
0
3
Order By: Relevance
“…The wear was quantified by weighing the cup. Moreover, the effect of titanium third bodies was tested in the HUT-4 with AoA, as it has been assumed that titanium third bodies may be one cause for squeak clinically [7]. The particles that were put between the bearing surfaces were made using a file from a titanium acetabular shell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wear was quantified by weighing the cup. Moreover, the effect of titanium third bodies was tested in the HUT-4 with AoA, as it has been assumed that titanium third bodies may be one cause for squeak clinically [7]. The particles that were put between the bearing surfaces were made using a file from a titanium acetabular shell.…”
Section: Methodsmentioning
confidence: 99%
“…These include steep inclination angle of the acetabular cup [2], laxity of the joint [3], increased loading due to obesity or high-demand activity [4], poor lubrication or dry sliding [5], and roughening of the bearing surfaces [6] for a number of reasons, including titanium third bodies [7]. The principal difficulty is in the anticipation of the clinical relevance of each exceptional condition, or combinations of them.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that squeaky hips are associated with younger active, heavier, and taller patients [36][37] . Parvizi et al revealed an association with a particular prosthetic design that enabled neck impingement on the metallic rim of the cup 38,39 . Similarly, Restrepo et al found a clear relationship between the prevalence of squeaking and the type of femoral component implanted 40 .…”
Section: Squeakingmentioning
confidence: 99%
“…Of those 20%, only 1% reported a recurring squeaking noise, and no one has been revised thus far [1]. It is important to consider positioning accuracy and the quality of implant design, and not all systems behave similarly in this regard [9]. Our patients are informed about the possible rare occurrence of joint noises.…”
Section: Clinical Faceoffmentioning
confidence: 99%
“…What do you tell patients, and what should surgeons know about the current state-of-the-art on this topic? Prof. Laurent Sedel: A CoC implant with an ill-fitting cup position or design may lead to noise generation [9]. Noises generated by dry contact (a condition caused by absence of lubricating film in the CoC articulation) may increase due to interposed metallic foreign bodies.…”
mentioning
confidence: 99%